KEBERMANFAATAN ZAKAT PRODUKTIF UNTUK PENINGKATAN KESEJAHTERAAN MUSTAHIQ LEMBAGA MANAJEMEN INFAQ SURABAYA - Robimadin, Cahya Nugeraha; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
Poverty is a problem in almost every country. One cause of poverty is the low level ofwelfare in the economic field. Productive zakah is a solution so that economicempowerment can overcome the problem of poverty. The aim of the research is analyzethe benefits of productive zakah on improving the welfare of mustahiq. The researchmethod used in this research is qualitative descriptive with fieldbased approach.Information and data resources in this research are Lembaga Manajemen InfaqSurabaya and Mustahiq who received productive zakah. Triangulation (observation,interview and documentation) is used to collect the data. The data in the research isanalysed through three step; data reduction, data presentation, and conclusion. Theanalysis shows that the distribution of productive zakat has various benefits for themustahiq. While welfare must be unacceptable with material abundance, it must bebalanced and oriented to the afterlife.